Sleep Disorder and Cardiovascular Risk Factors among Patients with Type 2 Diabetes Mellitus - Shim, Unjin; Lee, Hyejin; Oh, Jee-Young; Sung, Yeon-Ah (The Korean journal of internal medicine, 2011)
Sleep disorder (SD) is associated with an increased risk of cardiovascular disease and is more prevalent among individuals with type 2 diabetes mellitus. These health problems not only frequently coexist but also exacerbate each other. We conducted a cross-sectional study to estimate the prevalence of SD among diabetic patients and to investigate the relationship between SD and cardiovascular risk among these patients. We recruited 784 patients with type 2 diabetes and conducted a self-administered questionnaire. We assessed sleep quality using the Pittsburgh Sleep Quality Index and the risk of obstructive sleep apnea (OSA) using the Berlin Questionnaire. Additional information included blood pressure and metabolic profiles. Of the 784 diabetic patients, 301 (38.4%) patients had poor sleep quality, and 124 (15.8%) were at high risk for OSA. Patients at increased risk for OSA were more obese; they also had higher blood pressure, fasting plasma insulin levels, insulin resistance assessed by homeostasis model assessment (HOMA-IR), and serum triglycerides levels (p < 0.05). The frequency of risk for OSA was higher among obese patients compared with non-obese patients (34.8% vs. 9.4%, p < 0.05). Logistic regression analysis revealed that male sex and bone mass index were independent predictors of risk for OSA. SD was prevalent among type 2 diabetic patients, and OSA could aggravate their risk for cardiovascular disease. Clinical treatment of these patients should include evaluation and intervention for SD.